Anais Do XXVII Simpósio Brasileiro De Informática Na Educação (SBIE 2016) 2016
DOI: 10.5753/cbie.sbie.2016.490
|View full text |Cite
|
Sign up to set email alerts
|

Explorando Robótica com Pensamento Computacional no Ensino Médio: Um estudo sobre seus efeitos na educação

Abstract: Robotics workshops for basic education are often proposed for the improvement of teaching practices in different disciplines. However, the teaching of these workshops is too difficult given the deficiency of teachers and students education in Computational Thinking (CT) skills. Then, in order to improve the teaching and learning process in these workshops we propose a robotics course with emphasis on CT for High School in Paraíba SESI Schools. This work shows the statistical analysis of the effects of robotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…However, we used the Anthropological Theory of Didactic indirectly when we applied our educational process. In [Souza et al 2022], we showed our educational process based on the Anthropological Theory of Didactic and ER consolidated methodologies to teach sciences like LEGO ® Education [ZOOM 2010], besides our ER experiences [Souza et al 2016a, Souza et al 2016b, Isabelle M. L. et al 2019, Souza et al 2021b, Souza et al 2021c. In this study, we described the results of an intervention that observed how high school students develop CT skills with or without contact with our educational process.…”
Section: Related Workmentioning
confidence: 99%
“…However, we used the Anthropological Theory of Didactic indirectly when we applied our educational process. In [Souza et al 2022], we showed our educational process based on the Anthropological Theory of Didactic and ER consolidated methodologies to teach sciences like LEGO ® Education [ZOOM 2010], besides our ER experiences [Souza et al 2016a, Souza et al 2016b, Isabelle M. L. et al 2019, Souza et al 2021b, Souza et al 2021c. In this study, we described the results of an intervention that observed how high school students develop CT skills with or without contact with our educational process.…”
Section: Related Workmentioning
confidence: 99%
“…No estudo de Costa et al [11], estudantes (menores de 15 anos) foram analisados quantitativamente com o objetivo de avaliar o impacto do PC em uma abordagem conjunta com a Matemática, revelando um resultado positivo nas habilidades de resolução de problemas dos estudantes. No mesmo sentido, o trabalho apresentado por Souza et al [25] demonstrou que o ensino de robótica alinhada às habilidades de PC favorece positivamente o desempenho acadêmico de estudantes do EM.…”
Section: Trabalhos Relacionadosunclassified
“…Costa et al (2017) conducted a quantitative analysis with Brazilian students (under 15 years) to assess the impact of using CT in a joint approach with Mathematics obtaining positive results on students problem-solving skills. In the context of High School robotics, Souza et al (2016) demonstrated that teaching robotics aligned to CT skills had a positive impact on academic performance of High School students.…”
Section: Related Workmentioning
confidence: 99%